Characterization of lncRNA-Associated ceRNA Network to Reveal Potential Prognostic Biomarkers in Lung Adenocarcinoma - Wang, Yang; He, Ruyi; Ma, Lixin (Frontiers in Bioengineering and Biotechnology, 2020)
Lung adenocarcinoma (LUAD) is one of the most fatal malignant tumors harmful to human health. The complexity and behavior characteristics of long-noncoding RNA (lncRNA)-associated competing endogenous RNA (ceRNA) network in LUAD patients are still unclear. The purpose of this study was to elucidate the regulatory networks of dysregulated RNAs, view and identify potential prognosis signatures involved in LUAD. The expression profiles of mRNAs, lncRNAs, and miRNAs were obtained from the TCGA database. In total, 2078 DEmRNAs, 257 DElncRNAs and 101 DEmiRNAs were sorted out. A PPI network including 45 DEmRNAs was constructed. 10 hub genes in PPI network associated with cell cycle related pathways were identified and they played key roles in regulating cell proliferation. A total of 3 DEmiRNAs,7 DElncRNAs, and 6 DEmRNAs were enrolled in the ceRNA network. Except for certain genes without any published study reports, all the genes in ceRNA network played essential role in controling tumor cell prolieration and associated with prognistic in LUAD. Finally, based on step regression and Cox regression survival analysis, we identified four candidate biomarkers, including miR490, miR1293, LINC01740 and IGF2BP1, and establised a risk model based on the four genes. Our study provided a global view and systematic dissection of lncRNA-associated ceRNA network, and the identified four genes might be novel important prognostic factors involved in LUAD pathogenesis.